Paracrine Anti-inflammatory Effects of Adipose Tissue-Derived Mesenchymal Stem Cells in Human Monocytes - Guillén, Maria I.; Platas, Julia; Pérez del Caz, María D.; Mirabet, Vicente; Alcaraz, Maria J. (Frontiers in Physiology, 2018)
The inflammatory process is an essential phenomenon in the induction of immune responses. Monocytes are key effector cells during the inflammatory process. A wide range of evidence indicates that mesenchymal stem cells from adipose tissue (ASC) are endowed with immunomodulatory capacity. However, the interaction between ASC and monocytes in the innate immune response is not well understood. The aim of this work was to investigate the possible paracrine anti-inflammatory effects of ASC in human monocytes. Monocytes were isolated from buffy coats and ASC from fat of non-obese patients. Conditioned medium (CM) from ASC in primary culture was used. We have assessed the effects of CM on the production of inflammatory mediators, degranulation, migration, phagocytic activity, senescence, oxidative stress, mitochondrial membrane potential and macrophage polarization. We have shown that ASC exert paracrine anti-inflammatory actions on human monocytes. CM significantly reduced the production of TNFα, NO and PGE2 and the activation of NF-κB. In addition, we observed a significant reduction of degranulation, phagocytic activity and their migratory ability in the presence of the chemokine CCL2. The senescence process and the production of oxidative stress and mitochondrial dysfunction were inhibited by CM which also reduced the production of TNFα by M1 macrophages while enhanced TGFβ1 and IL-10 release by M2 macrophages. This study have demonstrated relevant interactions of ASC with human monocytes and macrophages which are key players of the innate immune response. Our results indicate that ASC secretome mediates the anti-inflammatory actions of these cells. This paracrine mechanism would limit the duration and amplitude of the inflammatory response.